Non-invasive Cognitive Enhancement in Epilepsy - Jacobs, Claire S.; Willment, Kim C.; Sarkis, Rani A. (Frontiers in Neurology, 2019)
Epilepsy patients frequently experience cognitive difficulties, particularly in the domains of memory, attention, and executive function. Despite the frequency of these difficulties among epilepsy patients, current strategies to treat cognitive dysfunction are limited. We performed a systematic review of controlled trials of noninvasive cognitive enhancement in epilepsy. We identified studies examining the efficacy of pharmacological agents, namely the acetylcholinesterase inhibitors donepezil and galantamine, the NMDA noncompetitive antagonist memantine, and the stimulant methylphenidate, as well as non-invasive nonpharmacological transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS). We highlight the data currently available and the limitations of the current literature.